2002
DOI: 10.1002/pfi.4140410806
|View full text |Cite
|
Sign up to set email alerts
|

HPT Models: An overview of the major models in the field

Abstract: AS THE FIELD of human performance technology (HPT) begins to gain more mainstream attention in the eyes of those charged with improving organizational efficiency, questions arise about how to put these concepts and theories into practice. Several recent articles (Langdon, 2000 ;Chevalier, 2000 ) have described how HPT can be used in an organization. This article aims to identify the major models in the field and examine the ideas and beliefs that have lead to their conception, development, and acceptance.For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The Deterline model positions the performer center stage (Whiteside, 1998); however, factors supporting the performer demonstrate the interplay between behavior and environmental structure, reminiscent of Gilbert's six dimensions (Wilmoth, Prigmore, & Bray, 2004). Wile's (1996) performance model is an integration of internal and external factors related to the performer and the environment.…”
Section: Subsequent Adaptations Of Gilbert's Modelmentioning
confidence: 98%
“…The Deterline model positions the performer center stage (Whiteside, 1998); however, factors supporting the performer demonstrate the interplay between behavior and environmental structure, reminiscent of Gilbert's six dimensions (Wilmoth, Prigmore, & Bray, 2004). Wile's (1996) performance model is an integration of internal and external factors related to the performer and the environment.…”
Section: Subsequent Adaptations Of Gilbert's Modelmentioning
confidence: 98%
“…Results from this case study show the value of applying the traditional HPT model for performance improvement in the university library setting and providing implications for practitioners to demonstrate the model's effectiveness and suitability to clients in any environment (Wilmoth, Prigmore, & Bray, 2002).…”
Section: Resultsmentioning
confidence: 93%
“…Based on this review, we suggested several important research gaps and future research directions for HRD scholars. As job design is an important theoretical foundation of the HRD field as well as an HRD intervention (Jacobs, 1990; Swanson, 2001; Wilmoth, Prigmore, & Bray, 2002), HRD researchers and practitioners should aim to build better bridges between job design and HRD. Organizations as well as individuals would benefit from this, as a more integrated understanding of job design and HRD would maximize employees’ well-being, safety, and performance through their crafting of their jobs.…”
Section: Resultsmentioning
confidence: 99%